Film Editing, Digital Montage, and the “Ontology” of Cinema - Furstenau, Marc (Cinémas, 2018)
This article offers an account of the advent of digital editing, or digital montage. While reference is often made in film theory to the “ontological” effects of technological change, the term itself is rarely defined in explicit fashion. Following the philosopher Gregory Currie, the author argues that an ontological analysis cannot begin from an accounting of any putatively necessary or definitive physical aspect of the cinema as a medium. Indeed, the author argues, following Noël Carroll, that the cinema is not a “medium,” but rather an art form that employs a wide range of media. In the transition from film editing to digital montage, the means for the creation of multimedia, audiovisual cinematic compositions have been consolidated in so far as most media are now rendered in digital form, allowing for more comprehensive and fine-grained manipulations and modifications. On the basis of a more adequate account of the ontology of the cinema, this can be seen as continuous with the history of film art.